Multiple atypical esophageal foreign bodies in an infant - Roma Varik; Attibele Mahadevaiah Shubha; Kanishka Das (Wolters Kluwer Medknow Publications, 2020)
Foreign body ingestion is a common accidental emergency in children. We report an unusual case of multiple blunt and sharp esophageal foreign bodies in a female infant probably associated with homicidal intent and its management.